Transformative Psychometric Research Trioengineering Modeling: Triangulating Digital Instrumentation, Implementation, and Data Analysis for Effective, Efficient, and Engaging Classroom Inquiry - Osler II, James Edward (Advances in Social Sciences Research Journal, 2020)
This monograph provides an in–depth discourse on “Research Engineering” in the field of “Educational Science” first detailed in a 2012 Journal on Mathematics article. Research Engineering involves the methodology and the metrics used to conduct in–depth research investigations via the innovative Total Transformative Trichotomy–Squared [Tri–Squared] Test. The triangulation of this test aids in the comprehension of how the Tri–Squared calculation is a mixed methods research design based upon “Trichotomous Psychometrics”. Trichotomous Psychometrics involves the development, deployment, and analysis of “Trifold Assessments” for the holistic transformation of qualitative outcomes into quantitative data. This paper is a continuation of the published article entitled: The Psychometrics of Educational Science: Designing Trichotomous Inventive Investigative Instruments for Qualitative and Quantitative for Inquiry.